SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JENIS KAYU METODE WP&TOPSIS (STUDI KASUS: SONA MEUBEL) - fazhri arif alvinnes; Wicaksono, Freddy; Widhiani, Pahla (INTI TALAFA, 2024)
This Decision Support System is designed to simplify the selection of wood types used as raw materials for furniture production at Sona Meubel. Sona Meubel is a business that manufactures various types of furniture, such as wardrobes, beds, dressing tables, and TV cabinets, primarily using wood. Previously, wood selection was based solely on visual assessments, which often led to errors in decision-making. The Weighted Product (WP) method is used to evaluate several alternatives based on specific criteria, while the TOPSIS method selects alternatives that are closest to the positive ideal solution. This system considers criteria such as texture, physical properties, strength, price, availability, and durability. Built as a web-based system using PHP and the Laravel framework with a MySQL database, it provides wood selection recommendations based on the criteria entered.   Keywords: Decision Support System, Furniture, Wood, WP, TOPSIS